(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The growing demand for functional confectionery products has encouraged the incorporation of natural plant-based ingredients with health-promoting properties into conventional sugar-based foods. The present study aimed to develop and evaluate a functional hard candy enriched with Cymbopogon citratus (lemongrass) extract. Fresh lemongrass leaves were processed using thermal and non-thermal extraction methods, and the extracts were incorporated into a standard hard candy formulation containing sucrose, liquid glucose, citric acid, and water. The developed candies were evaluated for their physicochemical characteristics, including moisture, total sugars, reducing sugars, ash, and titratable acidity, using standard AOAC methods. Sensory quality was assessed by twenty semi-trained panellists using a nine-point hedonic scale. The developed lemongrass candy exhibited desirable physicochemical properties, with moisture (2.05%), total sugars (93.2%), reducing sugars (23.8%), ash (0.28%), and titratable acidity (0.52%), all of which were within the acceptable range for hard-boiled confectionery. Sensory evaluation revealed that both formulations were well accepted. The candy prepared using thermally extracted lemongrass showed higher scores for appearance, texture, and overall acceptability, whereas the non-thermally extracted formulation received higher scores for colour, aroma, and taste, indicating better retention of natural volatile compounds. These findings demonstrate that the extraction method significantly influences the sensory characteristics of lemongrass candy while maintaining desirable physicochemical quality. The study concludes that Cymbopogon citratus can be successfully incorporated into hard candy to produce a functional confectionery with good storage stability, favourable sensory properties, and potential health benefits. The developed product offers a promising value-added herbal confectionery with potential for commercial application.